2021
DOI: 10.1007/s10484-020-09499-4
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Erectile Function in Younger Men: A Pilot Study

Abstract: Erectile dysfunction (ED) in younger men is an increasing concern. In middle aged and older men, ED was related to lower resting heart rate variability (HRV), but research in younger men is lacking. The present study examined, in a nonclinical sample of 105 men between 18 and 39 years, the association of ED with several parameters of resting HRV. Scores of the 5-item version of the International Index of Erectile Function (IIEF-5) below 22 were considered as indicating ED. Eighteen men (17.1%) reported ED (mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The lower HRV was also a psychophysiological correlate of ED in middle-aged and elderly men (Kessler et al, 2019). Specifically, the HF values of ED patients were lower and LF/HF ratios were higher than those of the controls (Lee et al, 2011;Shim et al, 2018;Costa et al, 2021). In this study, we still observed that there were high LF/HF ratios in all patients, but only patients with both CP/CPPS and ED exhibited significantly higher LF/HF ratio, the increased LF/HF ratio indicating that sympathetic activity is higher than parasympathetic activity (Shim et al, 2018;Kayacan et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The lower HRV was also a psychophysiological correlate of ED in middle-aged and elderly men (Kessler et al, 2019). Specifically, the HF values of ED patients were lower and LF/HF ratios were higher than those of the controls (Lee et al, 2011;Shim et al, 2018;Costa et al, 2021). In this study, we still observed that there were high LF/HF ratios in all patients, but only patients with both CP/CPPS and ED exhibited significantly higher LF/HF ratio, the increased LF/HF ratio indicating that sympathetic activity is higher than parasympathetic activity (Shim et al, 2018;Kayacan et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Both methods have a high correlation with sympathetic and parasympathetic structures, which are known to accurately measure cardiac baroreflex activity and autonomic activity (Kayacan et al, 2021). Previous studies have shown that an imbalance in ANS activity is associated with many urologic diseases, including CP/CPPS (Cho et al, 2011), LUTS (Choi et al, 2010;Shim et al, 2018), and ED (Chen et al, 2009;Lee et al, 2011;Costa et al, 2021). Our findings found that none of the timedomain parameters differed significantly, but on frequencydomain analysis, all patients, including patients with CP/CPPS, ED, or both, exhibited significantly lower HF than healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation